Building and Characterization of an Affordable diOlistic Device for Single‐Cell Labeling in Rodent and Non‐Human Primate Brain Slices. Issue 4 (17th April 2023) - Heffernan, Kate S.; Galvan, Adriana
Abstract: In the brain, cell morphology often reflects function and thus provides a first glance into cell‐specific changes in health and disease. Studying the morphology of individual cells, including neurons and glia, is essential to fully understand brain connectivity and changes in disease states. Many recent morphological studies of brain cells have relied on transgenic animals and viral vectors to label individual cells. However, transgenic animals are not always available, and in non‐human primate (NHP) models, viral transduction poses several practical and financial challenges, limiting the number of researchers that can thoroughly investigate cell morphology in NHP or other non‐transgenic animals. The diOlistic system for delivering fluorescent lipophilic dye‐coated gold or tungsten particles into brain tissue has been used to label single cells, but the currently available systems are expensive, have limited applications, and are rare in laboratories. Investigations of cell morphology without transgenic or viral approaches rely on immunohistochemical markers that may not reveal structural detail, such as in astrocytes. To overcome these practical limitations to expand our understanding of cell morphology across species with an emphasis on astrocytes, we constructed a low‐cost ballistic method to deliver dye‐coated gold or tungsten particles into NHP and rodent brain slices. We have optimized the tissue processing parameters to achieve penetration of DiI‐coated particles, allowing for the complete reconstruction of individual cells within a brain slice. While we report on astrocytes in rodent and NHP brain slices, this protocol can be adapted and implemented across species and tissue types to evaluate cell morphology. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Building the diOlistic device Basic Protocol 2 : Preparation of dye "bullet" carriers Basic Protocol 3 : Perfusion, brain sectioning, and diOlistic labeling Alternate Protocol : Immunohistochemical labeling of sections prior to diOlistic bombardment